JUDICIAL REASONING IN MARRIAGE DISPENSATION AT THE TAKENGON SYAR'IYAH COURT: A Critical Analysis of Legal Pluralism and The Paradox of Child Protection - Apriliansyah, Muhammad Akmal; Gulo, Azhar Nur Mawaddah; Subhan, Bentara (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
This study examines the judicial reasoning model in granting marriage dispensation at the Takengon Syar'iyah Court through a critical analysis of Decision Number 185/Pdt.P/2024/MS.Tkn. Using a socio-legal approach with legal pluralism and maqashid al-syariah frameworks, this research reveals that judges employ a three-stage hierarchical reasoning pattern: formal-procedural, social fact verification, and Islamic law substantive justification. The findings indicate that positive law (Law No. 16/2019 and PERMA No. 5/2019) functions as an initial barrier and procedural legitimizer, while Islamic law, particularly the fiqh maxim dar'u al-mafasid muqaddamun 'ala jalb al-mashalih (preventing harm takes precedence over bringing benefit), serves as a substantive problem-solver. Local socio-cultural realities, especially unplanned pregnancy and family honor concerns, act as triggering factors that are subsequently framed as "legal emergencies." This research identifies a critical paradox: the court's comprehensive advice on the risks of child marriage (educational disruption, mental health issues, and potential domestic violence) is ultimately overridden by the immediate need to resolve social crises. The study concludes that this practice represents "reactive legal pluralism" that effectively addresses immediate social conflicts but fails to provide proactive, long-term child protection, thereby reducing the "best interests of the child" principle to mere procedural formality rather than substantive consideration.